Analisis Pemanduan Traffic BIFA Terhadap Kelancaran Komunikasi di Perum LPPNPI Cabang Denpasar - Wahid Zulfikar, Muhammad Nabil; Praptiningsih, Nunuk (Jurnal Bisnis dan Operasi Penerbangan, 2023)
I Gusti Ngurah Rai Airport is one of the airports with the largest amount of traffic in Indonesia. This of course has an impact on the number of communication frequencies between Pilots and Air Traffic Controllers (ATC), especially during peak hours. The ATC at Perum LPPNPI Denpasar Branch often experience problems when communicating with BIFA's Visual Flight Rules (VFR) Traffic. The obstacle experienced was the poor quality of the BIFA Pilot's voice which was heard on the ATC radio, so that the ATC had difficulty receiving the information conveyed by the BIFA Pilot. This of course has an impact on the smooth communication of ATC with all pilots at the Denpasar Branch of Perum LPPNPI, thus disrupting the operational operation of air traffic. This study aims to provide suggestions for reviewing these problems, in order to improve the safety and smoothness of air traffic control at Perum LPPNPI Denpasar Branch.